Sports motivation: a narrative review of psychological approaches to enhance athletic performance - Alkasasbeh, Walaa Jumah; Akroush, Sofia Hwaishel (Frontiers in Psychology, 2025)
This narrative review examines the impact of psychological motivation on athletic performance by exploring the relationship between intrinsic motivation (IM) and extrinsic motivation (EM), and their respective effects on athletes. The primary aim is to understand how different types of motivation influence performance across various sports and to highlight the role coaches play in enhancing athlete motivation. The review draws on 97 studies published between 2001 and 2024, sourced from reputable academic databases such as Google Scholar, PubMed, Scopus, and PsycINFO. Included studies specifically addressed the effects of IM and EM on athletic performance and the influence of coaching strategies. Studies unrelated to sports performance or motivation were excluded. Findings indicate that intrinsic motivation rooted in personal goals, enjoyment, and self-determination has a more sustained and profound impact on athletic performance, promoting long-term commitment and continuous improvement. In contrast, extrinsic motivation driven by rewards, recognition, or social pressure tends to produce short-term gains but lacks enduring influence. The review underscores the pivotal role of coaches in fostering motivation by providing individualized feedback, cultivating a supportive and positive environment, and recognizing athlete efforts. Furthermore, a comparison between individual and team sports suggests that IM is more prevalent and influential in individual sports, whereas EM and social reinforcement play a larger role in team-based settings. The review concludes that a strategic combination of intrinsic motivation, external reinforcement, and a supportive social climate is essential for sustained athletic success. Coaches and sports programs should integrate these elements when designing motivational approaches tailored to their athletes’ needs.